2x - 3y + 4z + 9
2x - 3y = 6
2x= 6
moises2003:
O que vc quer saber?
Soluções para a tarefa
Respondido por
2
Se
![2x = 6 \\ x = 3 2x = 6 \\ x = 3](https://tex.z-dn.net/?f=2x+%3D+6+%5C%5C+x+%3D+3)
Então
![2x - 3y = 6 \\ 6 - 3y = 6 \\ y = 0 2x - 3y = 6 \\ 6 - 3y = 6 \\ y = 0](https://tex.z-dn.net/?f=2x+-+3y+%3D+6+%5C%5C+6+-+3y+%3D+6+%5C%5C+y+%3D+0)
E
![2x - 3y + 4z + 9 \\ 6 - 0 + 4z + 9 \\ 15 + 4z \\ 4z = - 15 \\ z = - \frac{15}{4} 2x - 3y + 4z + 9 \\ 6 - 0 + 4z + 9 \\ 15 + 4z \\ 4z = - 15 \\ z = - \frac{15}{4}](https://tex.z-dn.net/?f=2x+-+3y+%2B+4z+%2B+9++%5C%5C+6+-+0+%2B+4z+%2B+9+%5C%5C+15+%2B+4z+%5C%5C+4z+%3D++-+15+%5C%5C+z+%3D++-+%5Cfrac%7B15%7D%7B4%7D+)
Então
E
Perguntas interessantes